If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + -7 = -7 + 4s Reorder the terms: -7 + 6s = -7 + 4s Add '7' to each side of the equation. -7 + 7 + 6s = -7 + 7 + 4s Combine like terms: -7 + 7 = 0 0 + 6s = -7 + 7 + 4s 6s = -7 + 7 + 4s Combine like terms: -7 + 7 = 0 6s = 0 + 4s 6s = 4s Solving 6s = 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. 6s + -4s = 4s + -4s Combine like terms: 6s + -4s = 2s 2s = 4s + -4s Combine like terms: 4s + -4s = 0 2s = 0 Divide each side by '2'. s = 0 Simplifying s = 0
| 9m-24=60+5m | | 5(3x+5x)-3=112 | | 12x=3x-4 | | 3x*6x=450 | | 6x*25=150 | | 5x^6+12x-32=143 | | 2x^2=15 | | 5x*10x=4050 | | 5x*10x=2250 | | -16/8 | | 7h-6h=19 | | k/-8=6 | | n/-11=8 | | m/-9=20 | | k/-6=-12 | | n/3=-14 | | 18u-5u=14 | | x^4-8x^3+24x^2-32x+16=0 | | 1/4(12x-4)=-13 | | 18u-u-5u=14 | | -22X^5+50x^4+72x^3=0 | | 5x+x=25 | | 1/3(6x+18)=-24 | | 4(8x+7x)=90 | | 3m+-5m=12 | | 8d-d-3d+3d=14 | | -2x+1+6x=81 | | 19d+d-18d=14 | | 6y-y-5y+4y=20 | | 7v+3v-8v-2v+v=20 | | 2x+6x=81 | | 12-3x=2+5x |